Effect of dynamic injection pressure on performance, emission and combustion characteristics of a compression ignition engine. (December 2015) - Imtenan, S.; Ashrafur Rahman, S.M.; Masjuki, H.H.; Varman, M.; Kalam, M.A.
Abstract: Diesel engine emissions produced during burning of fossil fuel are extremely accountable for numerous serious problems. In order to lessen these emissions, performance of diesel engine needs to be improved. Fuel injection pressure is one of the operating parameters that affects the performance and emissions of a diesel engine which has been reported in this review paper. Decrease in injection pressure results in inferior combustion which leads to increase in BSFC and decrease in BTE. Injection pressure increase results in better mixing of air and fuel. As a result, combustion improves which leads to reduced BSFC and increased BTE. Due to superior air–fuel mixture resulting from increase in injection pressure, CO and HC emission decreases. Also, exhaust gas temperature decreases too. Increase in injection pressure results in increased heat release rate which leads increase in NO x emission. Literatures reports that, increasing the injection pressure results in up to 18% and 9% reduction of BSFC and EGT. Furthermore, it is possible to achieve more than 50% CO and HC and 28% NO x emission reduction by increasing the fuel injection pressure.